Return to Full Functioning after Graded Exercise Assessment and Progressive Exercise Treatment of Postconcussion Syndrome. (4th January 2012) - Baker, John G.; Freitas, Michael S.; Leddy, John J.; Kozlowski, Karl F.; Willer, Barry S.
Abstract : Exercise assessment and aerobic exercise training for postconcussion syndrome (PCS) may reduce concussion-related physiological dysfunction and symptoms by restoring autonomic balance and improving cerebral blood flow autoregulation. In a descriptive pilot study of 91 patients referred to a university clinic for treatment of PCS, a subset of 63 patients were contacted by telephone for assessment of symptoms and return to full daily functioning. Those who experienced symptoms during a graded exercise treadmill test (physiologic PCS, n = 40 ) were compared to those who could exercise to capacity (PCS, n = 23 ). Both groups had been offered progressive exercise rehabilitation. Overall 41 of 57 (72%) who participated in the exercise rehabilitation program returned to full daily functioning. This included 27 of 35 (77%) from the physiologic PCS group, and 14 of 22 (64%) from the PCS group. Only 1 of the 6 patients who declined exercise rehabilitation returned to full functioning. Interpretation of these results is limited by the descriptive nature of the study, the small sample size, and the relatively few patients who declined exercise treatment. Nonetheless, exercise assessment indicates that approximately one third of those examined did not have physiologic PCS.